Pemanfaatan Batu Gunung Ambeso Pada Campuran AC-Base - Irpan; Robert Mangontan; Alpius (Paulus Civil Engineering Journal, 2020)
This research is intended for testing the characteristics of AC-BASE mixes using Ambeso volcano rock. The method in this study is to conduct a series of rough, fine, and filler aggregate characteristics test and then design an AC-BASE mixture composition and Marshall testing to obtain mixture characteristics and Marshall immertion tests for obtain immersion index (IP) / residual tightness index (IKS) / durability of the optimum asphalt mixture. The results of research conducted at the Road and Asphalt Laboratory of the Faculty of Civil Engineering, Indonesian Christian University Paulus Makassar, showed that the characteristics of pavement materials in the form of ambeso mountain stone, gandangbatu sillanan sub-district met specifications as road pavement coating materials. Through the Marshall Test obtained the characteristics of a mixture of AC-BASE with asphalt content of 4.5%, 5%, 5.5%, 6%, 6.5%. The results of the Marshall immertion test of Laston AC-BASE mixture with optimum asphalt content of 5% obtained an Immersion Index (IP) / Residual Strength Index (IKS) / Durability of 96.06% meeting the requirements of at least 90%, meet the 2018 Highways Specifications.